Impact of Uric Acid on Hypertension Occurrence and Target Organ Damage: Insights From the STANISLAS Cohort With a 20-Year Follow-up. (8th April 2020) - Kanbay, Mehmet; Girerd, Nicolas; Machu, Jean-Loup; Bozec, Erwan; Duarte, Kevin; Boivin, Jean-Marc; Wagner, Sandra; Ferreira, João Pedro; Zannad, Faiez; Rossignol, Patrick
Abstract: BACKGROUND: Recent studies have shown that hyperuricemia may be associated with incident hypertension (HTN). We examined whether serum uric acid (SUA) is a predictor of HTN and target organ damage (TOD) 20 years later in initially healthy middle-aged individuals. METHODS: Participants from the Suivi Temporaire Annuel Non-Invasif de la Santé des Lorrains Assurés Sociaux (STANISLAS) a single-center familial longitudinal cohort study (961 initially healthy adults and 570 children) underwent clinical and laboratory measurements at baseline and after approximately 20 years. Blood pressure (BP: using ambulatory BP measurements), urine albumin-to-creatinine ratio, estimated glomerular filtration rate (eGFR), left ventricular hypertrophy (LVH), diastolic dysfunction, and carotid–femoral pulse wave velocity (PWV) were measured at the end of follow-up. RESULTS: In the parent population, higher baseline or last SUA levels and higher change in SUA (ΔUA) were significantly associated with an increased risk of HTN development, even after adjusting for known HTN risk factors (all P < 0.01). Higher baseline SUA was marginally associated with an increased risk of having high carotid–femoral PWV ( P = 0.05). The association of SUA with BP increase was body mass index dependent (the increase in BP being greater in leaner subjects; interactionp < 0.05), and the association of SUA with eGFR decline was age dependent (the decline in eGFR being greater in older subjects; interactionp < 0.05). There was no significant association between SUA and diastolic dysfunction or LVH. In the whole population (i.e. including children), a significant association between SUA at baseline and the risk of HTN and higher carotid–femoral PWV was also found (both P < 0.02). CONCLUSIONS: Increased SUA is associated with the development of HTN and vascular/renal TOD in initially healthy midlife subjects.